PENGARUH PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA TINGKAT AKHIR PRODI AKNTANSI DI UNIVERSITAS TEKNOLOGI DIGITAL - Mulyani, Syifa Aulia; Feriyanto, Oon (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 2 (2025): JISAMAR (March-May 2025)DO - 10.52362/jisamar.v9i2.1879, 2025)
This research aims to determine the influence of learning behavior on the level of understanding of accounting in final year accounting study program students at the Digitech University. A good understanding of accounting is very important for students to be successful in their professional careers. The method used in this research is quantitative, where data is collected through questionnaires distributed to all final year accounting student with the return of 81 respondents. The result of the analysis show that there is a positive and significant relationship between Learning Behavior and Accounting Understanding, with Study Behavior contributing 52% to the variation in Accounting Understanding. The most influentia dimension of Leaning Behavior is rational thingking. This is comfirms that students who implement good and efficient learning behavior tend to show a deeper understanding of accounting.